A Comprehensive Review of the Protein Subunit Vaccines Against COVID-19 - Heidary, Mohsen; Kaviar, Vahab Hassan; Shirani, Maryam; Ghanavati, Roya; Motahar, Moloudsadat; Sholeh, Mohammad; Ghahramanpour, Hossein; Khoshnood, Saeed (Frontiers in Microbiology, 2022)
Two years after severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), in December 2019, the first infections were identified in Wuhan city of China. SARS-CoV-2 infection caused a global pandemic and accordingly, 5.41 million deaths worldwide. Hence, developing a safe and efficient vaccine for coronavirus disease 2019 (COVID-19) seems to be an urgent need. Attempts to produce efficient vaccines inexhaustibly are ongoing. At present time, according to the COVID-19 vaccine tracker and landscape provided by World Health Organization (WHO), there are 161 vaccine candidates in different clinical phases all over the world. In between, protein subunit vaccines are types of vaccines that contain a viral protein like spike protein or its segment as the antigen assumed to elicit humoral and cellular immunity and good protective effects. Previously, this technology of vaccine manufacturing was used in a recombinant influenza vaccine (RIV4). In the present work, we review protein subunit vaccines passing their phase 3 and 4 clinical trials, population participated in these trials, vaccines manufactures, vaccines efficiency and their side effects, and other features of these vaccines.